165 Sharing leadership: current attitudes, barriers and needs of clinical and non-clinical managers in UK's integrated care system. (16th November 2020) - Alabi, Monica; Aufegger, Lisa; Darzi, Ara; Bicknell, Colin
Abstract : NIHR Imperial Patient Safety Translational Research Centre London UK Background: As systems become more complex, shared leadership (SL) has been suggested to have a dominant role in improving cross-functional working tailored to organisational needs. Little, however, is known about the benefits of SL in healthcare management, especially for UK's recently formed integrated care system (ICS). The aim of this study was to understand current attitudes, barriers and needs of clinical and non-clinical managers sharing leadership responsibilities in the ICS. Method: Twenty clinical and non-clinical leaders in fifteen organisations were interviewed to understand current cross-functional leadership collaborations, and the potential SL may have on the recently established ICS in the NHS. The data were transcribed and analysed thematically. Results: Findings showed perceptions and experiences of clinical and non-clinical healthcare management in relation to: (1) motivation to execute a leadership position, including the need to step up and a sense of duty; (2) attitudes towards interdisciplinary working, which is reflected in conflicts due to different values and expertise; (3) SL skills and behaviours, including the need for effective collaboration and communication by means of empathy, listening, and having a shared vision; and, (4) barriers to achieve SL in the ICS, such as bureaucracy, and a lack of time and support. Conclusions: SL may help improve current leadership cultures within the NHS; however, for SL to have a tangible impact, it needs to be delivered as part of leadership development for doctors in postgraduate training, and development programs for aspiring, emerging and established leaders, with clear lines of communication.